Impact of serum calcium levels on the occurrence of sepsis and prognosis in hospitalized patients with concomitant psoriasis: a retrospective study based on the MIMIC-IV database - Zheng, Xiaolong; Su, Qianjin; Wang, Yedi; Geng, Xuefeng (Frontiers in Immunology, 2025)
ObjectiveThis study aims to investigate the relationship between serum calcium levels during hospitalization and the incidence and prognosis of sepsis in hospitalized patients with psoriasis.MethodsA retrospective analysis of patients with concomitant psoriasis admitted for the first time was conducted, utilizing the Medical Information Mart for Intensive Care database. Machine learning techniques, along with logistic regression, Cox regression, group-based trajectory modeling (GBTM), and mediation analysis, were employed to assess the influence of serum calcium levels and other clinical indicators on the occurrence of sepsis and all-cause mortality.ResultsSerum calcium exhibits a significant inverse correlation with the occurrence of sepsis [odds ratio (OR) =0.351, 95% CI: 0.265-0.463, P<0.001]. Furthermore, serum calcium levels exhibited a negative correlation with 90-day all-cause mortality [hazard ratio (HR)=0.594, 95% CI: 0.422-0.835, P=0.003] and a similar negative correlation with 365-day mortality risk (HR=0.642, 95% CI: 0.502-0.821, P<0.001). Platelet counts mediated the relationship between serum calcium and both 90-day and 365-day all-cause mortality, accounting for 24.6% and 22.0% of the mediation effect, respectively. Additionally, three distinct trajectory patterns based on serum calcium levels were identified, with the low calcium trajectory group exhibiting a higher risk of sepsis (OR=2.400, 95% CI: 1.163-5.068, P<0.001).ConclusionSerum calcium levels serve as a significant predictive factor for the occurrence and prognosis of sepsis in hospitalized patients with psoriasis. Continuous monitoring of serum calcium levels and timely correction of hypocalcemia may contribute positively to improving patient outcomes.